Manufacturing company turnaround during the covid-19 pandemic - Andita Sulistyowati (International Journal of Applied Finance and Business Studies, 2023)
The financial distress situation experienced by several Indonesian companies has led them to work diligently in achieving corporate turnaround. However, this has been exacerbated by the presence of the COVID-19 pandemic, which not only affects Indonesia but the world as a whole, resulting in a sluggish global economy. This research aims to examine the influence of management ownership, independent commissioners, and free assets on corporate turnaround during the COVID-19 pandemic. The research sample consists of 45 manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021, selected through purposive sampling. The analysis method employed in this study is logistic regression analysis. The research findings indicate that managerial ownership does not significantly affect corporate turnaround. On the other hand, independent commissioners and free assets have a significant and positive influence on corporate turnaround.